Memaksimalkan Potensi Dan Pemasaran UMKM Dengan Memanfaatkan Marketplace Bukalapak dan Tokopedia - Huda, Miftahul; Abid, Awaludin (PT. Karya Inovatif Nusantara, 2024)
MSME marketing strategy by utilizing the marketplace is a very important step in facing the current digital era. In the post-pandemic period, one effort that can be made is to create and socialize a promotion system by marketing online. One means of online marketing is by maximizing the use of the marketplace. The method for implementing this community service activity is using the experiential learning method. The aim of this community service activity is to provide an understanding of the importance of the marketplace, provide an understanding of business potential through the Bukalapak and Tokopedia marketplaces, provide an understanding of marketing through the Bukalapak and Tokopedia marketplaces and provide an understanding of creating a brand in online marketing. The conclusion from this community service activity is that using the marketplace as an effective marketing channel can help MSMEs reach a wider range of consumers, increase sales and strengthen their position in an increasingly competitive market.